Biosorción de cromo total en soluciones ideales utilizando una matriz de microalgas nativas inmovilizadas en alginato cálcico - Armas Jara, Erick Steve (2017)
Native microalgae (Chlorella sp.) of La Libertad were used in this research, these were cultured in lab scale aerated bioreactors, then these were immobilized in calcium alginate (Matrix), and used on 100 mL of an aqueous solution with 100 ppm of initial total Chromium concentration, using a Batch system, in order to define the influence of pH, Contact time, mass and recycle on the total chromium removal percent. The obtained results concluded that microalgae improve the biosorption process, being pH 4 more effective, in 6 hours of contact time and an optimal mass of 3 grams; however it isn’t viable its reuse by using as a desorbent 0.1 M HNO3 for 6 hours. Therefore, we conclude that microalgae are an promising and envaironmentaly friendly option on the treatment of effluents contaminated with chromium